Electronic structure of c-axis controlled α-Fe2O3 thin film probed by soft-X-ray spectroscopy. (14th April 2016) - Kawamura, Kinya; Suzuki, Naoya; Tsuchiya, Takashi; Yamaguchi, Shohei; Ochi, Masanori; Suetsugu, Takaaki; Minohara, Makoto; Kobayashi, Masaki; Horiba, Koji; Kumigashira, Hiroshi; Higuchi, Tohru
Abstract: We have prepared c -axis controlled α-Fe2 O3 thin films on Al2 O3 substrates by RF magnetron sputtering and studied their electronic structure by soft-X-ray spectroscopy. The lattice constant of c -axis increases with increasing film thickness due to the relaxation of lattice mismatch between α-Fe2 O3 and Al2 O3 and formation of oxygen vacancies. The electrical conductivity is higher in thicker thin film. The valence band consists of t2g - and eg -subbband of Fe 3d state hybridized with O 2p state. The band gaps of ∼25 and ∼95 nm thicknesses of Fe2 O3 thin film are ∼1.8 and 1.4 eV, respectively, which correspond to the activation energy of electron conductivity. The above results indicate that the band gap and the conductivity of α-Fe2 O3 thin film directly affect the change of the lattice constant of c -axis and formation of oxygen vacancies.